Pseudohypoparathyroidism during pregnancy and the postpartum period: A case series of five patients - Wang, Jia-Jia; Yang, Yi; Wang, Ya-Bing; Song, An; Jiang, Yan; Li, Mei; Xia, Wei-Bo; Liu, Yan-Ping; Wang, Ou; Xing, Xiao-Ping (Frontiers in Endocrinology, 2022)
Objectives Pseudohypoparathyroidism (PHP) is a rare disease, especially when combined with pregnancy. We aimed to explore the changes in serum calcium/parathyroid hormone (PTH) level and medical treatment in a case series of PHP during pregnancy and the postpartum period. Methods A total of five PHP patients with six pregnancies were enrolled. The classification of PHP was based on (epi)genetic analysis. Clinical characteristics, biochemical indices, and treatment strategies before, during, and after pregnancy were retrospectively collected. Results All patients received calcium and vitamin D agents with nearly normal serum calcium before pregnancy except patient 2 who was found hypocalcemic during gestation. All patients chose Cesarean section, and one suffered preterm delivery due to oligoamnios. The neonatal birth weight ranged from 2,250 to 4,300 g, and all neonates were free of hypocalcemia-related symptoms. The change in calcium metabolism was inconsistent including stable, improved, or worsened during pregnancy. Serum PTH level remained low in the first two trimesters in patients with stable and improved conditions while increased in the last two trimesters in patients with a worsened condition. Serum calcium changed inconsistently while PTH increased consistently during lactation. For patients who did not breastfeed, calcium homeostasis improved after delivery. Conclusion Calcium homeostasis and medicine dosage changed differently in PHP patients during pregnancy and lactation. However, most patients had good pregnancy outcomes. Serum PTH levels might predict changes in calcium metabolism during pregnancy.